Desain UI/UX SIAKAD dengan Metode Design Thinking pada Universitas Katolik Indonesia Santu Paulus Ruteng - Putri, Devita Maulina; Adil, Madre Volenta (J-INTECH (Journal of Information and Technology), 2023)
SIAM is a web-based academic information system application at Santu Paulus Ruteng Catholic University of Indonesia with the aim of providing academic-based information to students. Currently, SIAM has a problem with the declining number of visitors. This is because the view from SIAM is less attractive and less responsive to the mobile display of the web. So the purpose of the design of this information system to be able to provide services and a form of appearance that is attractive so that users often access. Troubleshooting is done by designing a dedicated user interface/user experience for mobile devices using the Design Thinking method. The test was carried out to 36 students at the Catholic University of Indonesia Santu Paulus Ruteng with usability testing using the System Usability Scale method. The test results were obtained that the prototype designed received a very good category (Acceptable) which means that the system can be accepted very well in terms of user interface/ user experience so that prototypes can be easily used first on a mobile display.